Engaging patients in medication reconciliation via a patient portal following hospital discharge. (13th September 2013) - Heyworth, Leonie; Paquin, Allison M; Clark, Justice; Kamenker, Victor; Stewart, Max; Martin, Tracey; Simon, Steven R
Abstract: Few ambulatory medication reconciliation tools exist. Transitions between inpatient and outpatient care can result in medication discrepancies. An interdisciplinary team designed a new 'Secure Messaging for Medication Reconciliation Tool' (SMMRT) within a patient web portal and piloted it among 60 patients at a Veterans Affairs hospital, an integrated system with a shared electronic health record. Recently discharged patients used SMMRT to view their medications in a secure email message and replied using SMMRT's interactive form, verifying their medication regimens and clarifying any inaccuracies. In total, 108 medication discrepancies and 23 potential adverse drug events (ADEs) were seen. Nearly 50% of the potential ADEs were classified as serious. Overall, participants were enthusiastic about SMMRT; 90% said they would use SMMRT again. Enabling patients to conduct medication reconciliation through a web portal is feasible in the transition from inpatient to outpatient care and may improve medication safety.